2016
DOI: 10.1016/j.jrras.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of the natural radioactivity and radon exhalation rate in some cements used in India and its radiological significance

Abstract: The presence of natural radioactivity and radon exhalation from building materials contribute to the radiation dose received by human. So, it is essential to evaluate the activity levels of the primordial radionuclides (238 U, 226 Ra, 232 Th and 40 K) present in the building materials for the assessment of natural radiation dose. Cement is one of the major component of the building materials and is used on a large scale. In the present study, the commercially available cement samples of fifteen different brand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The results of this work are in good agreement with the results of a previous study of building materials conducted in Nigeria (3) . Even the specific activities for cement are in line with results published elsewhere (11)(12)(13)(14)(15)(16)(17)(18)(19) . In contrast, the analyzed samples of sand in this study show a distinctly higher specific radioactivity than in other studies (19)(20)(21)(22)(23) , except for 40 K that reported two values which are higher by factors of 1.18 (China) and 1.50 (South Korea), respectively.…”
Section: Comparison Of Activity Concentrations Of 226 Ra 232 Th and supporting
confidence: 91%
“…The results of this work are in good agreement with the results of a previous study of building materials conducted in Nigeria (3) . Even the specific activities for cement are in line with results published elsewhere (11)(12)(13)(14)(15)(16)(17)(18)(19) . In contrast, the analyzed samples of sand in this study show a distinctly higher specific radioactivity than in other studies (19)(20)(21)(22)(23) , except for 40 K that reported two values which are higher by factors of 1.18 (China) and 1.50 (South Korea), respectively.…”
Section: Comparison Of Activity Concentrations Of 226 Ra 232 Th and supporting
confidence: 91%
“…The maximum value for activity concentration index is 2 (I ≤ 2) to meet 0.3 mSvyr −1 dose criterion and I ≤ 6 to meet 1 mSvyr −1   26,27 .…”
Section: Methodsmentioning
confidence: 99%
“…The origin of these materials is the Earth's crust, but they find their way into building materials, air, water, food and the human body itself. The world wide average indoor effective dose due to gamma rays from building materials is estimated to be about 0.4 mSv per year [ [3] , [4] ]. Globally, building materials that contain radioactive nuclides have been used for many decades.…”
Section: Methods Detailsmentioning
confidence: 99%